2002
DOI: 10.1191/0267659102pf528oa
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol in cardioplegia as an oxygen free radical scavenger measured by malondialdehyde

Abstract: Oxygen free radicals (OFRs) are associated with ischaemia-reperfusion injury involving many organs, including the heart, which can lead to depressed cardiac function and abnormalities in the cardiac ultrastructure. This is seen upon the release of the aortic crossclamp when the ischaemic myocardium is reperfused in patients undergoing cardiopulmonary bypass (CPB). Various studies have shown that by adding OFR scavenging agents or antioxidants to the CPB prime or cardioplegia, cardiac performance improves. Mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…CxI produces deleterious ROS during I/R [22] and has also been identified as a target for oxidative damage probably due to ROS-mediated oxidation of cardiolipin, a phospholipid required for optimal function of CxI [23]. Cs, which afforded more protection against CxIsustained oxidative phosphorylation, has high mannitol and glutathione content, which can contribute for an enhanced ROS scavenging [24,25]. Although CxI activity was preserved, a decrease in protein oxidation was not observed in Cs preservation, which may indicate that the ROS that cause disturbance of CxI-sustained oxidative phosphorylation are not counteracted by the antioxidant species in the cardioplegic solution, either because of limited access to the site of production or because of limited enrichment in the mitochondrial membranes, which in theory is the site where oxidative damage to proteins will occur.…”
Section: Discussionmentioning
confidence: 99%
“…CxI produces deleterious ROS during I/R [22] and has also been identified as a target for oxidative damage probably due to ROS-mediated oxidation of cardiolipin, a phospholipid required for optimal function of CxI [23]. Cs, which afforded more protection against CxIsustained oxidative phosphorylation, has high mannitol and glutathione content, which can contribute for an enhanced ROS scavenging [24,25]. Although CxI activity was preserved, a decrease in protein oxidation was not observed in Cs preservation, which may indicate that the ROS that cause disturbance of CxI-sustained oxidative phosphorylation are not counteracted by the antioxidant species in the cardioplegic solution, either because of limited access to the site of production or because of limited enrichment in the mitochondrial membranes, which in theory is the site where oxidative damage to proteins will occur.…”
Section: Discussionmentioning
confidence: 99%
“…In studies showing reduced edema and neuroprotection by mannitol, dosages typically range between 1.0 -1.5 g/kg and produce a hypertonic bolus (e.g., Filbert et al, 1993;Ueno et al, 1994;Berger et al, 1994;Bareyre et al, 1997;Korenkov et al, 2000). However, mannitol has been reported to possess free radical scavenging properties (e.g., Willis et al, 1994;Jiang et al, 2001;Larsen et al, 2002) which may have provided an extra measure of neuroprotection. Interestingly, it was observed that body temperatures in the soman + diazepam + dantrolene group were lowered below 33 °C (i.e., 31.9 ± 0.78 °C) for more than 10 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Der δ-Opioid-Rezeptor-Agonist DAla2-D-Leu5-Enkephalin (DADLE) wirkt über eine direkte Stimulation des δ-Opioid-Rezeptors [47] und führt letztlich zur Bildung von Sauerstoffradikalen [41], welche eine pharmakologische Präkonditionierung triggern. Mannitol ist dagegen als wirkungsvoller Radikalfänger beschrieben [18,29]. Wegen seiner osmotischen Eigenschaften wird Mannitol andererseits kardioplegischen Lösungen zugesetzt und in der Herzchirurgie verwendet.…”
Section: Introductionunclassified